Identification of potential serum and urine biomarkers for patients with prostate cancer using lectin-based proteomic analyses / Jaime Jacqueline Jayapalan - Jaime Jacqueline, Jayapalan (2015)
The lack of specificity of prostate specific antigen emphasizes the need for a highly specific, sensitive and reliable marker with effective diagnostic predictability in curbing prostate cancer (PCa) at an early stage. In the present study, candidate protein biomarkers were identified when serum and urine samples of patients with PCa, those with benign prostatic hyperplasia (BPH) and controls (for the latter) were profiled using gel- and lectin-based proteomics approaches. In the first part of the study, significantly reduced levels of apolipoprotein AII and complement C3 beta chain fragment were demonstrated in the profiles of patients with PCa when their neat serum and those with BPH patients were separately subjected to two-dimensional electrophoresis (2-DE) and image analysis. Subsequently, when 2-DE resolved sera of subjects were electrotransferred onto NC membrane, probed with enzyme-conjugated champedak galactose binding (CGB) lectin and analysed by densitometry, only inter-alpha-trypsin inhibitor heavy chain 4 fragment (ITIH4f) was found to be significantly reduced in abundance in PCa patients. Alternatively, when pooled serum of patients were subjected to affinity isolation using immobilized CGB lectin and analysed by 2-DE and densitometry, enhanced abundance of high molecular weight kininogen, alpha-1-antitrypsin and transthyretin were detected in sera of PCa patients compared to those with BPH. In the second part of the study, when acetone-precipitated urine of PCa and BPH patients as well as age-matched controls were separately subjected to 2-DE and image analysis, significantly lower abundance of urinary saposin B and two different fragments of ITI light chain (ITIL), namely, ITILf1 and ITILf2, were demonstrated in PCa patients compared to controls. Abundance of ITILf2 fragment was also found to be significantly decreased in patients with PCa compared to BPH patients. When image iv analysis was similarly performed on 2-DE resolved urinary proteins that were electrotransferred on NC membranes and detected using CGB lectin, ITIH4f was significantly enhanced in urine of PCa patients compared to controls. This finding was in contrast to the data observed in sera of PCa subjects. In the final part of the study, pooled serum and urine obtained from patients with BPH and PCa as well as controls were subjected either to lectin- or immuno-blotting techniques and densitometric analysis, as a means of validation. When probed with enzyme-conjugated CGB lectin or anti-bikunin + trypstatin antibody, levels of abundance of serum ITIH4f and urinary proteins including ITIH4f, ITILf1 and ITILf2 of subjects were generally comparable with the previously generated data via 2-DE, with little variation in levels of significance. However, when taken together as indices, densitometric ratio of (i) serum to urinary ITIH4f, (ii) urinary ITIH4f to ITILf1 and (iii) urinary ITIH4f to ITILf2 peptide fragments showed marked segregating differences in indices for different groups of subjects. Furthermore, individual mean ratio indices between all PCa and BPH patients or controls were found not to overlap thus, highlighting strong discriminatory powers of the indices in effectively differentiating PCa from non-cancer conditions. Nonetheless, potential use of these indices as diagnostic markers in early detection of PCa requires prior extensive validation on clinically representative populations.